2013
DOI: 10.2176/nmc.53.438
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategies for Nonenhancing Slow-Growing Gliomas With Special Reference to Functional Reorganization: Review With Own Experience

Abstract: Nonenhancing intrinsic brain tumors have been empirically treated with a strategy that has been adopted for World Health Organization (WHO) grade II gliomas (low-grade gliomas: LGGs), even though small parts of the tumors might have been diagnosed as WHO grade III gliomas after surgery. However, the best surgical strategy for nonenhancing gliomas, including LGGs, is still debatable.LGGs have the following features: slow growth, high possibility of histologically malignant transformation, and no clear border be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
0
5
0
1
Order By: Relevance
“…Several reports have suggested that brain function plasticity occurs preoperatively in patients with low-grade gliomas, based on the findings of functional magnetic resonance imaging (fMRI) and positron emission tomography (PET). 82 88) Prior fMRI and PET studies have demonstrated activation of motor and language areas within and around the tumor. 89 , 90) These reports indicate that the infiltrative characteristics of low-grade gliomas may make it possible for the neurologic function to persist within the tumor, while the slow rate of tumor invasion likely promotes functional plasticity.…”
Section: Brain Functional Plasticitymentioning
confidence: 99%
“…Several reports have suggested that brain function plasticity occurs preoperatively in patients with low-grade gliomas, based on the findings of functional magnetic resonance imaging (fMRI) and positron emission tomography (PET). 82 88) Prior fMRI and PET studies have demonstrated activation of motor and language areas within and around the tumor. 89 , 90) These reports indicate that the infiltrative characteristics of low-grade gliomas may make it possible for the neurologic function to persist within the tumor, while the slow rate of tumor invasion likely promotes functional plasticity.…”
Section: Brain Functional Plasticitymentioning
confidence: 99%
“…One proposed mechanism for enhancing extent of resection of dominant insular gliomas by intraoperative mapping is brain plasticity and functional reorganization of brain areas involved in important tasks (6,30). This has been previously demonstrated in gliomas of extra-insular locations (31).…”
Section: -Extent Of Tumor Removalmentioning
confidence: 81%
“…В настоящее время существует много работ, касающихся изучения перестройки речевой функциональной системы у больных с инсультами [8,[26][27][28], при оперативном лечении больных с фармакорезистентной эпилепсией [23,29], а также у больных с опухолями головного мозга [30,31]. Например, A. Thiel и соавт.…”
Section: рис 2 фмрт пациента с глиомой правой лобной доли: двустороunclassified